Konstruksi Model Bimbingan Kelompok Hibrida Menggunakan Teknik Rekonstruksi Kognitif Berbasis Nilai "Ngudi Kasampurnan": Validasi Berbasis Ahli - Zamroni, Edris; Lestari, Indah; Gudnanto, Gudnanto; Kholik, Kholik; Ferdiansyah, Handy; M, Usman; Lio, Stefanus; Solo III, Mark P. (Pamomong: Journal of Islamic Educational Counseling, 2024)
The need to ground guidance and counseling theory following the character of Indonesia, where strong cultural values in everyday life characterize the people, needs to be addressed positively in developing strategies for guidance and counseling services for school students. This research aims to validate the group guidance model using a hybrid mode using the Ngudi Kasampurnan value-based cognitive reconstruction technique, developed to provide group guidance services to high school students. This research uses the ADDIE model development research type to validate the model developed. The instrument used was expert validation with Aiken's V analysis method as interrater agreement. Model validation was carried out on eight experts, including 3 group guidance experts, three cognitive technique experts, and two cultural experts who have a qualified understanding of Sunan Kalijaga's teachings. The validation results from group guidance experts concluded that the model developed was very feasible for testing. Furthermore, cognitive technique experts in guidance and counseling services also provided the same assessment with a few notes on the possibility of cognitive disputes, which might be biased if done online. Cultural experts also evaluate that the values of ngudi kasampurnan that have been explored also fulfill and represent the overall values taught by Sunan Kalijaga. In general, the validator states that the model that has been developed meets the requirements for limited testing. Furthermore, it is necessary to create a wider use of local Indonesian wisdom so that Indonesian guidance and counseling services become more characterized.